The effect of metacognitive awareness toward lecturer's peformance - Muhamad Galang Isnawan (STKIP PGRI Banjarmasin, 2019)
The implementation of the Tridharma of Higher Education and the fulfillment of supporting elements is an obligation that must be carried out by lecturers in higher education as a form of reflection of its performance. Many factors influence the performance, one of which is metacognitive awareness. Therefore, the purpose of this study is to describe the effect of metacognitive awareness toward lecturer’s performance in universities. This type of research is ex-post facto. The population of this study was all lecturers at the UNW Mataram with a sample of all lecturers at the FKIP UNW Mataram. The sampling technique used is stratified random sampling. Data analysis used is regression analysis (R Square, F test, and t test). Based on the results of the study obtained information that metacognitive awareness influences the performance of lecturers in universities. The value of R Square obtained is 70.7%; F value of 77,177 with a significance of 0,000; and the value of t obtained is 8.785 with a significance of 0,000.